Species-Specific Interferon-Gamma Release Assay for the Diagnosis of Mycobacterium abscessus Complex Infection - Steindor, Mathis; Stehling, Florian; Olivier, Margarete; Kehrmann, Jan; Diricks, Margo; Maurer, Florian P.; Horn, Peter A.; Straßburg, Svenja; Welsner, Matthias; Sutharsan, Sivagurunathan; Lindemann, Monika (Frontiers in Microbiology, 2021)
Mycobacterium abscessus complex (MABC) infection has a devastating impact on the course of cystic fibrosis (CF) and non-CF lung disease. Diagnosis of MABC pulmonary disease is challenging, and current diagnostic approaches lack accuracy, especially in CF. In this study, we aimed to establish an MABC-specific interferon-γ release assay to detect host immune responses to MABC and improve diagnostics of MABC infection by the detection of antigen-specific T cells. Four species-specific proteins of MABC were overexpressed in an Escherichia coli expression system. Purified proteins were used to stimulate peripheral blood mononuclear cells of study subjects in an ELISpot assay. Interferon-γ response of 12 subjects with established diagnosis of MABC infection (10 CF and two non-CF) was compared with 35 controls (22 CF and 13 non-CF) distributed to three control groups, 17 CF subjects without NTM infection, nine subjects with NTM infection other than MABC, and nine subjects with tuberculosis. Cellular in vitro responses in the MABC group were stronger than in the control groups, especially toward the protein MAB_0405c (39 vs. 4 spots per 300,000 PBMC, p = 0.004; data represent mean values) in all patients and also in the subgroup of CF subjects (39 spots vs. 1 spot, p = 0.003). Receiver operating characteristic curve analysis indicated that spot numbers of at least 20 were highly predictive of MABC infection (all patients: area under curve 0.773, sensitivity 58%, and specificity 94%; CF patients: area under curve 0.818, sensitivity 60%, and specificity 100%). In conclusion, we identified MAB_0405c as a protein that may stimulate MABC-specific interferon-γ secretion and may add to the diagnosis of MABC infection in affected patients.